Tipologi Amaliyah Nahdlatul Ulama dan Persatuan Islam dalam Membangun Ukhuwah Islamiyyah - Parlina, Ika; Supriadi, Udin (PT. Student Rihlah Indonesia, 2025)
The purpose of this research is to analyze the typology of amaliyah of Nahdlatul Ulama and Islamic Unity in building Ukhuwah Islamiyyah. This research uses a qualitative approach and literature study method. Based on the results of the discussion, human understanding of the teachings of Islam continues to develop throughout the ages and gives birth to various religious views. These various religious views also developed in Indonesia accompanying the process of broadcasting and preaching Islam. Two Islamic community organizations, namely Nahdlatul Ulama and Islamic Unity, have differences in the issue of amaliyah. Among the issues that often arise and trigger debate in the midst of Indonesian society are the problems of shalawat, prayer intention, qunut subuh, grave pilgrimage, tahlilan, maulid nabi, tarawih prayer, and hand gestures during tayahud. It is hoped that after knowing each difference of opinion on the amaliyah of Nahdlatul Ulama and Persis as Muslims can respect these differences of opinion so that ukhuwah Islamiyyah will be realized in the midst of the people, because each Islamic organization has arguments that can be accounted for.